Analisis Quality of Service (QoS) Jaringan Internet untuk Optimalisasi Bandwith - Imam Ghozali, Muhammad; Alif Catur Murti; Syafiul Muzid (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The rapid growth in internet use in recent years has placed significant demands on the quality of network services. Technological developments and increasingly complex communication needs make it important to improve the Quality of Service (QoS) of internet networks. Optimal Quality of Service is critical to supporting critical applications such as video conferencing, streaming, and other real-time applications. Obstacles such as high latency, low Throughput, and lack of prioritization in traffic management can hinder the user experience and reduce the effectiveness of the service. Carrying out QoS optimization not only ensures that critical services get the right priority, but can also increase the overall efficiency of using network resources. The involvement of this prioritization scheme in the network infrastructure provides a holistic solution, combining a deep understanding of latency, Throughput and priority requirements. All of this is done in an effort to optimize QoS so that users can get a good experience in using internet access.